Bicycling and tricycling road race performance in international UCI events between 2011 and 2019 - Borg, D. N.; Osborne, J. O.; Tweedy, S. M.; Liljedahl, J. B.; Nooijen, C. F. (SportRxiv Preprints, 2020)
Purpose: This study described bicycling (C-classes, 1-5) and tricycling (T-classes, 1-2) performance in International Cycling Federation (Union Cycliste Internationale; UCI) road race events between 2011 and 2019. Methods: A total of 3,243 race results (bicycling = 2,571; tricycling = 672) from 33 UCI events held between May 2011 and August 2019 were included in the analysis. Mean race velocity was calculated for each race result. Bicycling and tricycling data were separately modelled using hierarchical regression. Cohen`s d was calculated for the standardised difference between adjacent classes. Results: Road race performance was statistically different between men`s classes C1/C2 (p <.001; d = 0.42), C2/C3 (p <.001; d = 0.47) and C3/C4 (p <.001; d = 0.73). In contrast, performance was not statistically different between men`s C4/C5 (p = .506; d = 0.14), or between all adjacent women`s bicycling classes (p = .050 to .121; d = 0.46 to 1.15). The absence of statistical differences between adjacent women`s bicycling classes may be due to the relatively small number of observations in these classifications. As expected, race performance was statistically different between T1 and T2 for men (p <.001; d = 1.64) and women (p <.001; d = 1.38). Conclusion: Road race performance was hierarchical within the disciplines of bicycling and tricycling, with higher classes characterised by faster mean velocities. However, not all adjacent classes were statistically different. Future research should examine the influence of prosthetic technologies and the impact of different impairments on bicycling and tricycling performance.